Growing lemons and cherries? Pre- and post-acquisition performance of foreign-acquired firms in new EU member states - Jože Damijan; Črt Kostevcz; Matija Rojec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
Foreign acquisitions are an increasingly important mode of FDI in the new EU member states (NMS). Using firm-level data and a common estimation framework for seven NMS we study pre-and post-acquisition perfirmance of acquired firms. We find that selection criteria of target firms differ significantly across countries. In some countries the evidence supports the idea of ?cherry picking? with better firms being chosen as targets for acquisition, while in the others ?lemons?with growth potential tend to get selected. Regardless of whether ?cherries?or ?lemons?are targeted, perfirmance of acquired firms improved after the acquisition, whereby the boost in productivity has not been achieved by a reduction in employment, as it even increased, but rather by increased e ciency in the use of labor and especially capital. Additionaly, foreign ownership is found to yield biggest rewards to small less productive firms.
Keywords: F23; D22; 330; cross-border mergers and acquisitions; firm productivity; picking lemons